The Impact of Public Health Insurance on Household Credit Availability in Rural China: Evidence from NRCMS - Yang, Qing (Int J Environ Res Public Health, 2020)
A large body of literature has shown that the burden of healthcare can push individuals and households into the burden of medical care and income loss. This makes it difficult for rural or low-income households to obtain and use safe and affordable formal credit services. In 2003, China’s government implemented a new rural public health insurance, which was called the New Rural Cooperative Medical Scheme (NRCMS). This study provides evidence of the impact of NRCMS on household credit availability using the China Family Panel Studies (CFPS) for 2010. The tobit regression approach and mediator model are used. The results show that, as a public health insurance system sustained by the participation of government investment, the NRCMS provides good “collateral” and significantly enhances rural households’ formal credit availability level. Furthermore, this positive effect is mainly reflected in the economic effect of NRCMS. Our results are robust to alternative statistical methods. Our findings suggest that expanding access, fulfilling the NRCMS mortgage function, and providing more financial services for rural households would have big benefits with regard to easing credit constraints for rural residents.